Pengaruh Metode Isolasi Terhadap Komposisi Proksimat, Sifat Pasting dan Morfologi Pati Sekoi (Setaria italica (L)P. Bauv) Varietas Lokal Bengkulu: Pengaruh Metode Isolasi Terhadap Komposisi Proksimat, Sifat Pasting dan Morfologi Pati Sekoi (Setaria italica (L)P. Bauv) Varietas Lokal Bengkulu - Fitri Electrika Dewi Surawan; Eni Harmayani; Nurliyani Nurliyani; Djagal Wiseso Marseno (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Several research on foxtail millet  starch have been studied, but there is no recommended method for isolation of foxtail millet starch.  In this study, isolation of Bencoolen foxtail millet  starch, using sodium hidroxyde with 1x, 2x and 3x cycles, hexane-Sodium hydroxide treatment, and destilled water were done. The purpose of this study were to determine  isolation method of Bencoolen foxtail millet starch which  minimum impurities, pasting and morphological properties. This research was conducted with a randomized complete design with isolation method as a factor. The result of this study shown that method of starch isolation with NaOH 0.3% three cycle, produces the highest  of starch and amylose content  were 83.15%  and 19.40%. The  moisture, ash, protein,  fat and crude fiber content of foxtail millet starch  were  8.48%, 0.47%, 4.45%, 0.09%, and 0.21%,   respectively. The gelatinization temperature, peak time, viscosity, and break down viscosity value  of this starch  were 78 oC, 7.6 minutes,  4228 cp, and  2738 cp,  respectively. It has the highest brightness (L*),  and polygonal shape of starch granule.